2021
DOI: 10.1109/access.2021.3075140
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Analysis of Machine Learning Algorithms for Crime Prediction Using Stacked Generalization: An Ensemble Approach

Abstract: Ensemble learning method is a collaborative decision-making mechanism that implements to aggregate the predictions of learned classifiers in order to produce new instances. Early analysis has shown that the ensemble classifiers are more reliable than any single part classifier, both empirically and logically. While several ensemble methods are presented, it is still not an easy task to find an appropriate configuration for a particular dataset. Several prediction-based theories have been proposed to handle mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…In relation to this research, our primary goal is to produce a model that could be useful to the law enforcement unit and to our civilians (More et al, 2021). Our objective is to train our model to accurately classify and forecast the crime category using the test data by using a dynamic ensemble classification algorithm (Keerthi R et al, 2020;Kshatri et al, 2021).This, in turn, could help in planning the deployment of the police force in the area with a high probability of crime occurrences so that it can be prevented prior.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to this research, our primary goal is to produce a model that could be useful to the law enforcement unit and to our civilians (More et al, 2021). Our objective is to train our model to accurately classify and forecast the crime category using the test data by using a dynamic ensemble classification algorithm (Keerthi R et al, 2020;Kshatri et al, 2021).This, in turn, could help in planning the deployment of the police force in the area with a high probability of crime occurrences so that it can be prevented prior.…”
Section: Methodsmentioning
confidence: 99%
“…(Safat et al, 2021) applied various machine learning techniques to predict more than 35 crime types in Chicago and Los Angeles, such as logistic regression, SVM, Naïve Bayes, KNN, decision tree, MLP, random forest, and XGBoost, and time series analysis evaluated with RMSE and MAE by LSTM and ARIMA model to fit the crime data better. (Kshatri et al, 2021) revealed that the assemble-stacking-based crime prediction method (SBCPM) based on the SVM algorithm achieves domain-specific configurations compared with another machine learning model, J48, SMO Naïve byes bagging, and the Random Forest. They also proved that any empirical data on crime is compatible with criminological theories and suggested that the prediction accuracy of the stacking ensemble model is higher than that of the individual.…”
Section: Related Workmentioning
confidence: 99%
“…Support Vector Machine (SVM) is a supervised learning algorithm that is based on a statistical theory. Support vector machines (SVMs) are a promising machine learning technique that has demonstrated excellent performance in the majority of prediction tasks [67]. The experiment done by [68] was combining SVM with Resnet50 demonstrated the greatest classification rate in experiments.…”
Section: Classificationmentioning
confidence: 99%
“…(ADA) and gradient boosting regression tree algorithm (GBRT), extreme gradient boosting algorithm (XGB) based on the idea of gradient boosting, light gradient boosting machine algorithm (LGBM) based on gradient boosting decision tree, and also considered traditional machine learning models such as support vector regression (SVR), arti cial neural networks (Multilayer perceptron was selected in this study, MLP. ), k-nearest neighbors (KNN), etc., and linear regression (LR) models that have been proven to be a way to improve model effectiveness (Kshatri et al, 2021;Rooney et al, 2007).…”
Section: Data Preprocessingmentioning
confidence: 99%